2018
DOI: 10.17550/akademikincelemeler.430713
|View full text |Cite
|
Sign up to set email alerts
|

Orta Geli̇r Tuzaği: Yapisal Kirilmalar Altinda E7 Ülkeleri̇ İçi̇n Ampi̇ri̇k Bi̇r İnceleme

Abstract: Özİktisat literatürünün yeni ve ilgi çeken konularından biri orta gelir tuzağıdır. Orta gelir tuzağı, genel olarak orta gelirli ülkelerin yavaş büyüme performansı sergileyerek belirli gelir seviyesinde sıkışması ve yüksek gelir grubuna geçememesi olarak tanımlanabilir. Bu çalışmanın amacı, gelişmekte olan ülkeler arasında önemli yere sahip E7 (Gelişen 7) ülkelerinin orta gelir tuzağında olup olmadığını araştırmaktır. Bu kapsamda Robertson ve Ye (2013) yaklaşımı dikkate alınmıştır. Ampirik analizler tek ve iki … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…As many previous studies following the similar approach have shown (e.g. Koçak & Bulut 2014;Bozkurt et al, 2014;Keskingöz & Dilek, 2016;Tıraşoğlu & Karasaç 2018;Manga et al, 2019), the unit root findings of the present study also indicate that Turkey is not a MIT country. The stochastic convergence between Turkey and the US is significant and it can be said that the income gap between Turkey and US tends to decrease.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As many previous studies following the similar approach have shown (e.g. Koçak & Bulut 2014;Bozkurt et al, 2014;Keskingöz & Dilek, 2016;Tıraşoğlu & Karasaç 2018;Manga et al, 2019), the unit root findings of the present study also indicate that Turkey is not a MIT country. The stochastic convergence between Turkey and the US is significant and it can be said that the income gap between Turkey and US tends to decrease.…”
Section: Resultssupporting
confidence: 87%
“…(2014), Keskingöz and Dilek (2016), Tıraşoğlu and Karasaç (2018), Manga et al (2019) also empirically indicated that Turkey is not a MIT country. Ayala et al (2013) examined the income convergence of 17 LA countries with US.…”
Section: Literature Reviewmentioning
confidence: 99%